2015
DOI: 10.1016/j.jmaa.2015.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Big slices versus big relatively weakly open subsets in Banach spaces

Abstract: We study the unknown differences between the size of slices and relatively weakly open subsets of the unit ball in Banach spaces. We show that every Banach space containing c 0 isomorphically can be equivalently renormed so that every slice of its unit ball has diameter 2 and still its unit ball contains nonempty relatively weakly open subsets with diameter arbitrarily small, which answers an open question and stresses the differences between the size of slices and relatively weakly open subsets of the unit ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The answer is no, in fact, every Daugavet-point in D B has a weak neighborhood of arbitrary small diameter. Let us remark that the first example of a Banach space with the local diameter two property, but failing the diameter two property was given in [BGLPRZ15]. While we have used binary trees, their construction used the tree of finite sequences of positive integers and they even showed that every Banach space containing c 0 can be renormed to have the local diameter two property and fail the diameter two property.…”
Section: A Space With 1-unconditional Basis and Daugavet-pointsmentioning
confidence: 99%
“…The answer is no, in fact, every Daugavet-point in D B has a weak neighborhood of arbitrary small diameter. Let us remark that the first example of a Banach space with the local diameter two property, but failing the diameter two property was given in [BGLPRZ15]. While we have used binary trees, their construction used the tree of finite sequences of positive integers and they even showed that every Banach space containing c 0 can be renormed to have the local diameter two property and fail the diameter two property.…”
Section: A Space With 1-unconditional Basis and Daugavet-pointsmentioning
confidence: 99%
“…Thus the SD2P implies that every non-empty relatively weakly open subset of B X has diameter 2, which in turn implies that every slice of B X has diameter 2. None of these implications is reversible ( [5], [12]).…”
Section: Introductionmentioning
confidence: 99%
“…These properties, which are extremely opposite to the Radon-Nikodým property, have been deeply studied over the last few years. For instance, it was recently proved [3,4] that each one of the above properties is different from the rest in an extreme way.…”
Section: Introductionmentioning
confidence: 99%